Survivor and Caregiver Expectations and Preferences Regarding Lung Cancer Treatment - Wieland, Jana (Int J Part Ther, 2019)
PURPOSE: Treatment success in lung cancer is no longer restricted to objective measures of disease-specific outcomes and overall survival alone but now incorporates treatment morbidity and subjective quality of life (QoL). This study reports how lung cancer patients, survivors, and caregivers define treatment success and prioritize treatment decisions. MATERIALS AND METHODS: An online survey with both ranking and free-response questions was administered among lung cancer survivors and caregivers. Responses were used to evaluate treatment priorities, perceptions of treatment success based on Eastern Cooperative Oncology Group (ECOG) Performance Status, and troublesomeness of treatment-related toxicities. RESULTS: Among 61 respondents (29 lung cancer survivors, 28 caregivers of survivors, and 4 who were both survivors and caregivers), cancer cure was the highest priority when making treatment decisions for 74.5% of respondents, with QoL during and after treatment ranking second and third. Seventy percent of respondents felt that treatment morbidity resulting in complete dependence on others and spending the entire day confined to bed or chair would represent unsuccessful treatment. Requiring oxygen use was ranked as a very or extremely troublesome treatment toxicity by 64%, followed by shortness of breath (62%), fatigue (49%), chronic cough (34%), and appetite loss (30%). Even with remission, a 3- to 7-day hospital admission for pneumonia during treatment was deemed an unsuccessful outcome by 30%. CONCLUSION: This study highlights the importance of physicians discussing in detail with their lung cancer patients their desires and goals. Accounting for factors like expected performance status following treatment, troublesomeness of treatment toxicities, and hospitalization rates may help guide treatment decisions.